The Meaning of Media : Texts and Materiality in Medieval Scandinavia. - Horn, Anna Catharina; Johansson, Karl G. (Berlin/Boston : Walter de Gruyter GmbH, 2021)
Variance characterises the textual culture of the Middle Ages on all levels. Analysing this variance is paramount to understand the norms and transformations involved in the process of establishing a literate culture. This series focuses on the literate output in the Nordic region, from the perspective of Modes of Modification. In order to place the region in a larger context, it also encourages comparative studies with a wider European view.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books